2017
DOI: 10.1037/spq0000145
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effectiveness of a culturally adapted social-emotional intervention for African American males in an urban setting.

Abstract: The purpose of the present study was to assess the efficacy of a culturally adapted version of the Strong Start intervention program on the social-emotional outcomes of African American male students. Externalizing behavior problems of children, specifically African American males, are of great concern for schools. Punitive discipline polices such as expulsion and suspension have proved to be ineffective and harmful. Consequently, school-based social-emotional learning (SEL) interventions have been proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 42 publications
(51 reference statements)
4
64
3
Order By: Relevance
“…A review of the literature revealed a void of school‐based interventions specifically designed to address the unique obstacles of students of color (see Graves et al., ; Ryan et al., ). Currently, in the field of school psychology, there is a need to develop more culturally relevant interventions that can be used at the school level.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature revealed a void of school‐based interventions specifically designed to address the unique obstacles of students of color (see Graves et al., ; Ryan et al., ). Currently, in the field of school psychology, there is a need to develop more culturally relevant interventions that can be used at the school level.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, none of the programs exposed their students to the only culturally focused strength‐based measure, the Behavioral Assessment for Children of African Heritage (BACAH). The identification of culture‐specific strengths and within‐group research on success is emerging (Aston & Graves, ; Graves, ; Graves et al., ). For instance, Castro‐Olivo () recently modified a version of the Strong Teens intervention program for Latino students.…”
Section: Discussionmentioning
confidence: 99%
“…Strength‐based assessment is the measurement of emotional and behavioral assets and characteristics that enhances an individual's sense of accomplishment and promotes his or her social and academic development (Rashid & Ostermann, ). There is emerging evidence that the development of personal strengths is associated with decreasing relational aggression (Belgrave et al., ), increasing life satisfaction (Park, Peterson, & Seligman, ), and resilience (Graves et al., ). Despite the fact that there are documented benefits of strength‐based practices (SBPs), there is a dearth of research that has focused on the training and valid assessment of these practices.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Black students are 2.2 times more likely to be subjected to school‐related arrests in comparison to their White peers (U.S. Department of Education Office for Civil Rights, ). These issues are exacerbated in urban communities (Graves et al., ; Graves, Proctor, & Aston, ). Cumulatively, these issues eventually lead to the school‐to‐prison pipeline (Stevens‐Watkins & Graves, ).…”
Section: Introductionmentioning
confidence: 99%